Tinjauan Hadits Terhadap Fenomena Social Climber - Adelia Lutfiani; Muhammad Alif; Badrudin Badrudin; Khairil Ikhsan Siregar (Jurnal Studi Al-Qur'an, 2025)
Social Climber is a phenomenon where individuals strive to elevate their social status through various means, becoming an integral part of society's social dynamics. This research examines the phenomenon of social climbing from the perspective of hadith, the primary source of Islamic teachings. This study employs a qualitative approach using hadith thematic and grounded theory methods by investigating how Prophet Muhammad SAW viewed and guided his followers regarding seeking attention. Primary data is sourced from reliable digital hadith collections, while secondary data is derived from scholarly works related to the research topic. Data analysis combines both methods to identify key themes within hadith related to social climbing. This research aims to provide an understanding of social climbing behavior within the context of thematic hadith studies. By referencing hadith with similar themes or objectives, this study seeks to establish the Islamic legal basis for social climbing behavior, define and analyze the conflicting values associated with such actions, and explore how a Muslim should respond. Thus, the findings of this research aim to provide insights into how Islam views social climbing behavior and how a Muslim should react appropriately to it.